Rare and recurrent chromosomal abnormalities and their clinical relevance in pediatric acute leukemia of south Indian population - Seyed Hashem Mir Mazloumi; Prasanna Kumari; D S Madhumathi; L Appaji (Indian Journal of Medical and Paediatric Oncology)
Background and Objectives: This cytogenetic study detects a wide variety of common, rare and novel chromosomal abnormalities in patients with hematological disorders, providing valuable diagnostic and prognostic information. Materials and Methods: We addressed the utility of the cytogenetic technique in 50 patients of pediatric acute leukemia prospectively. Results: Successful cultures were found in 44 patients (88%) and abnormal karyotypes in 22 (44%). The common abnormalities like hyperdiploidy, del(6q), t(1;19)(q23;p13), t(4;11)(q22;q23), t(9;22)(q34;q11), rare t(2;7)(q23;p11) and t(4;12)(q21;p13) and a novel translocation t(7;9)(q22;q21) were observed in acute lymphoblastic leukemia. In acute myeloid leukemia, t(8;21)(q22;q22), del(16)(q22), t(15;17)(q22;q21) and t(9;11)(p22;q23) were commonly seen. Conclusion: Chromosomal abnormalities of this small group of patients are compared with the relevant literature with respect to the incidence rate and prognosis.